A 4-d Water Intake Intervention Increases Hydration and Cognitive Flexibility among Preadolescent Children. Issue 12 (2nd September 2019) - Khan, Naiman A; Westfall, Daniel R; Jones, Alicia R; Sinn, Macie A; Bottin, Jeanne H; Perrier, Erica T; Hillman, Charles H
ABSTRACT: Background: Hydration effects on cognition remain understudied in children. This is concerning since a large proportion of US children exhibit insufficient hydration. Objective: This study investigated the effects of water intake on urinary markers of hydration and cognition among preadolescents. Methods: A 3-intervention crossover design was used among 9- to 11-y-olds [ n  = 75 (43 males, 32 females); 58.2 ± 28.5 BMI percentile]. Participants maintained their water intake [ad libitum (AL)] or consumed high (2.5 L/d) or low (0.5 L/d) water for 4 d. The primary outcomes were performance on cognitive tasks requiring inhibition, working memory, and cognitive flexibility assessed using a modified flanker, go/no-go, and color-shape switch tasks, respectively. Secondary outcomes included urine hydration indices [i.e., color, urine specific gravity (USG), osmolality] assessed using 24-h urine collected during day 4 of each intervention. Repeated-measures ANOVAs were used to assess intervention effects. Results: There was a significant difference in hydration across all 3 interventions. Urine color during the low intervention [median (IQR): 6 (2)] was greater than during AL [5 (2)], and both were greater than during the high intervention [18 (0)] (all P  ≤ 0.01). Similarly, osmolality [low (mean ± SD): 912 ± 199 mOsmol/kg, AL: 790 ± 257.0 mOsmol/kg, high: 260 ± 115 mOsmol/kg] and USG [low (mean ± SD): 1.023 ± 0.005, AL: 1.020 ± 0.007, high: 1.005 ± 0.004] during the low intervention were greater during AL, and both were greater than during the high intervention (all P  ≤ 0.01). USG and osmolality AL values were related to switch task measures (β: 0.21 to −0.31, P  < 0.05). Benefits of the high intervention were observed during the switch task, whereby participants exhibited 34% lower working memory cost relative to the low intervention. No significant changes in cognition were observed for the flanker and go/no-go tasks. Conclusions: The water intervention improved urinary markers of hydration and had selective benefits during task switching. Furthermore, children's cognitive flexibility selectively benefits from greater habitual hydration and water intake. This study is registered at clinicaltrials.gov as NCT02816450.